No effect of ocean acidification on growth, photosynthesis, or dissolved organic carbon release by three temperate seaweeds with different dissolved inorganic carbon uptake strategies. (10th January 2023) - Paine, Ellie R; Britton, Damon; Schmid, Matthias; Brewer, Elizabeth A; Diaz-Pulido, Guillermo; Boyd, Philip W; Hurd, Catriona L
Abstract: In a future ocean, dissolved organic carbon (DOC) release by seaweed has been considered a pathway for organic carbon that is not incorporated into growth under carbon dioxide (CO2 ) enrichment/ocean acidification (OA). To understand the influence of OA on seaweed DOC release, a 21-day experiment compared the physiological responses of three seaweed species, two which operate CO2 concentrating mechanisms (CCMs), Ecklonia radiata (C. Agardh) J. Agardh and Lenormandia marginata (Hooker F. and Harvey) and one that only uses CO2 (non-CCM), Plocamium cirrhosum (Turner) M.J. Wynne. These two groups (CCM and non-CCM) are predicted to respond differently to OA dependent on their affinities for C i (defined as CO2 + bicarbonate, HCO3 − ). Future ocean CO2 treatment did not drive changes to seaweed physiology—growth, C i uptake, DOC production, photosynthesis, respiration, pigments, % tissue carbon, nitrogen, and C:N ratios—for any species, regardless of C i uptake method. Our results further showed that C i uptake method did not influence DOC release rates under OA. Our results show no benefit of elevated CO2 concentrations on the physiologies of the three species under OA and suggest that in a future ocean, photosynthetic CO2 fixation rates of these seaweeds will not increase with C i concentration.